ENSAIOS SOBRE MÚSICA E CONSTRUÇÕES CONTEMPORÂNEAS: compreensão musical por meio da apreciação - Gomes, Erica Dias (2014)
This research aimed to reflect about contemporary music understanding in collective educational processes by means of musical appreciation. Therefore, we designed a pedagogical and musical planning based on EMA aproach - Expressive Musical Appreciation - by Zuraida Bastião. To prepare this approach, group experiences were made, based on proposals to develop the listening of the sonorous environment, association of sounds to movements, and also proposals that could provide more integration between the research individuals. For this purpose, were chosen as the main theoretical references: Murray Schafer, John Paynter and Aston Peter and Bernadette Zagonel. The development of the proposals took into account the three principles defended by Keith Swanwick for music education. 21 contemporary songs were selected, which seek to show the most diverse contexts. The "Group of experiences in music appreciation" was formed as an university extension project at the Universidade Estadual do Centro Oeste - UNICENTRO, considering the greater flexibility provided by non-formal educational processes. The participatory research, of qualitative nature, had the action research influences, by the group`s way of actingin in relation to stance of the researcher, who also had theoretical support on the idea of the "Ignorant Master", proposed by Jacques Rancière. The group was composed of five members, with students and teachers, linked to art and education. The group participated in five meetings and various activities in which developed the pedagogical and musical proposal. To collect relevant information to this research were performed: diagnostic questionnaire; notes taken by researcher; audio and video recordings of practices and discussions throughout the process; and interview. "Instuition of the instant" by Gastón Bachelard, "The ignorant schoolmaster" by Jacques Rancière, ideas about cyborg culture by Bill Green and Chris Bigum, and ideas about contemporary music and its listening by José Miguel Wisnik were taken in order to analyse results. So, there was an increase in the group`s repertoire, as in musical knowledge as in the forms of relating to music. The whole group expanded ways of expressing responses to music listening, and it was possible to relate many musical issues by testimonials and productions made by group participants. It is possible to conclude that there was significant understanding of some characteristics as: techniques, materials and compositional processes; esthetic options and features of the production context. Finally, the study shows the idea, that listening can produce experience that joins the fictional at social reality, leading to different contexts, through transient displacements.